THE CIVIL NON-PERSECUTION AGREEMENT IN ADMINISTRATIVE MISCONDUCT ACTIONS (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2022)
The purpose of this paper is to analyze the institute of the Civil Non-Persecution Agreement as a consensual means applicable to the Law of Administrative Improbity, especially after the enactment of Law No. 13.964 / 19 (Anticrime Package). For this purpose, the deductive method was used, the nature of the research is qualitative and the selected procedure is the monograph. Still related to methodological issues, the research techniques refer to the bibliographic and legal. It started from the premise in which, if the aforementioned legislative novelty was able to put an end to the differences regarding self-composing means in the scope of administrative matters, since, previously, there was an express provision to prohibit any transaction in these cases. It was noted that, at present, there are no doubts as to the Civil Non-Persecution Agreement in relation to the Improbity Law, however, there are several problems regarding the regulation of this institute. In addition, as it is in the public interest, any solution must be based on this, under penalty of contradicting the national order, and not only, the entire anti-corruption microsystem must be taken into account.